Possibilities and importance of applying learning through research with children in the community: Pre-school teacher's perspective - Stepić Gordana M.; Dedaj Marta D.; Džaić Biljana M. (Sinteze)
Starting from the perception of a child as a researcher from the very birth, the research nature of his/her learning, the importance of the community for the learning and development of a preschool child, the goal of this research is to consider pre-school teachers' perspective and learning opportunities through research with children in the community. The research used descriptive method and research technique - scaling. The following research instrument was used: an assessment scale. Twenty pre-school teachers participated in the research. The research indicates that learning through research with children in the community is integrated into the educational process, that pre-school teachers recognize and know the value of this approach and that they mostly have the support of the community. The importance is also highlighted of recognizing challenges through reviewing practice and dealing with them in order to work continuously on improving learning through research with children in the community.